(5,10,15,20-Tetra(4-pyridil)porphinato)manganes(III) acetate modified by four mu(3)-oxo-triruthenium acetate clusters: synthesis, characterization, electrochemical behavior and catalytic activity - Dovidauskas, S.; Toma, H. E.; Araki, K.; Sacco, H. C.; Iamamoto, Y. (Elsevier B.V., 2000)
A novel supermolecule constituted by four mu(3)-oxo-triruthenium acetate clusters coordinated to manganese(III)-meso -tetra(4-pyridil)porphyrin acetate ([MnTPyP]CH3COO) has been synthesized. Characterization has been performed by UV-Vis and H-1 NMR spectroscopy. The electrochemical behavior (cyclic voltammetry and spectroelectrochemistry) in N,N'-dimethylformamide has been analyzed in terms of five redox processes: three related to peripheral clusters (Ru-IV,Ru-III,Ru-III/Ru-III,Ru-III,Ru-III/Ru-III,Ru-II,Ru-II) and two centered on the Mn-porphyrin core ((MnP)-P-III/(MnP)-P-II/(MnP2-)-P-II). A direct comparison has been performed between MnTCP and MnTPyP as catalysts for the cyclooctene and cyclohexane oxidation reactions. The improved selectivity exhibited by the supramolecular catalyst for cyclohexane oxidation has been ascribed to electronic effects on the oxomanganese(V) porphyrin species induced by the four peripheral clusters, in the formal (RuRuRuIII)-Ru-IV-Ru-III oxidation state. (C) 2000 Elsevier B.V. S.A. All rights reserved.
Keywords: electrochemistry; catalytic oxidation; manganese complexes; porphyrin complexes; ruthenium complexes; oxo-bridged complexes; cluster complexes